ADAPTASI DAN NEGOSIASI PADA PERKAWINAN ORANG KOMERING BERDASAR PENDEKATAN STRUKTURAL FUNGSIONAL - Sani, Amilda (Balai Arkeologi Sumatera Selatan, 2018)
Marriage in Indonesian is full of values and cultural rules that govern how marriagesshould be done. The marriage becomes the arena of conflict between individual or familyinterests. This paper will look at how these interests generate the various variants of marriageowned by the Komering community in the Cempaka and Batu areas. The adaptationand negotiation resulted the model of the wedding: (1) rasan tuha elder gawi, (2) rasan tuhatakad padang, (3) ngakuk anak, and (4) sibambangan. This variant model of marriage isresult of adaptation and negotiation between the right of the parent do determine the matefor her child, the parent's right to set the money request and dowry as a form of parentalconsent to her child's mate.